Leading schools as complex systems: exploring a new strengths-based approach - Johnson, Michael Ian (Frontiers in Education, 2025)
IntroductionEducation has become a complex and unpredictable landscape, creating a need for a paradigm shift in school leadership from deficit-based “firefighting” to designing new, strengths-based approaches that can effectively address emerging challenges in modern educational environments.MethodsThis qualitative exploratory study introduces a Strengths-Based Inquiry System (S-BIS), designed to identify attractive quality indicators through appreciative inquiry questioning. The model aims to help school leaders foster a culture of responsiveness within their schools.ResultsThe study examines the application of a strengths-based methodology to understand how Attractive Quality (AQ), Appreciative Inquiry (AI), and the creation of positive customer affect, through appreciative thinking, can support school leaders in developing more responsive approaches to leading schools as living systems.DiscussionFindings suggest that this integrated strengths-based approach offers school leaders an effective method for shifting from static, deficit-oriented mindsets to more dynamic, appreciative, and regenerative ways of thinking, critical for navigating the complexities inherent in leading schools as adaptive, living systems.